Onychocryptosis: a retrospective study of clinical aspects, inflammation treatment and pain management using Ozoile as a hydrogel and cream formulation - Vincenzo Francavilla; Giuseppe Secolo; Marianna D'Armetta; Rosario Toscano; Angelo Campo; Valentina Catanzaro; Marina Manno; Innocenzo Secolo; Giuseppe Messina (PAGEPress Publications, 2024)
Ingrown toenails account for roughly 20% of all foot problems in primary care. It is most common in young men, with nail care habits and footwear being major contributors. Onychocryptosis is typically caused by self-treatment attempts to cure the condition in its early stages. Its clinical features are frequently confused with other osseous and soft tissue abnormalities. The goal of this study was to provide perspectives on the management of pain and inflammation in Onychocryptosis using an Ozoile-based hydrogel formulation in a semi-occlusive bandage for 14 days, while incorporating natural pharmacological solutions into established protocols. The primary outcomes measured were pain reduction on NRS and stadiation according to the Al Kline Classification. The reduction was statistically significant, with a mean decrease in VAS score from 10 to 4 (p < 0.05), and Al Kline classification decreased by an average of 1.6 stages. 42% of patients recovered within the first 15 days of treatment, and 93% by the end of the scheduled treatment.